Damage Depth Test and Numerical Simulation of Stope Floor in Mining Face - Xipeng Cui; Hongqi Shao; Kailei Zhao (Geofluids)
The purpose of this study is to explore the development depth of rock layer rupture and analyze the developmental regularity of mining floor in Dongsi mining area of Xinzhi Coal Mine. Two kinds of pressure water testing methods and numerical simulation are used to study the failure characteristics of the bottom plate of the working face in Dongsi mining area of Xinxian Coal Mine. The results show that the failure of working face bottom plate starts from a certain range in front of the working face. With the advance of working face, the failure depth of mining bottom plate increases continuously. At the same time, the failure range of mining roadway is slightly larger than the failure range of working face bottom plate due to the double disturbance of tunneling and mining. The pressure water test shows that the rupture depth occurs at 8.98-9.03 m. The numerical simulation results of floor failure depth show that its depth is about 8.7 m, which is basically consistent with the pressure water test. It provides a reference for the advanced preexploration of mining bottom plate failure in similar coal seam.